﻿TLR7 Gln11Leu single nucleotide polymorphism in patients with sarcoidosis - ﻿Bordignon, M.; ﻿Bargagli, E.; ﻿Agostini, C.; Cinetto, F.; Baldo, V.; Alaibac, M.; Rottoli, P. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2013)
Sarcoidosis is a multi-factorial systemic disease with increased activity of the cellular immune components which is responsible of the formation of non-caseating granulomas in involved organs. Recent views on the etiology indicate interactions between inherited susceptibility and environmental or lifestyle factors. Concerning genes that may influence susceptibility to sarcoidosis Toll-like receptors (TLRs) may represent plausible candidates. In this present study, we investigated the X-linked TLR7 rs179008/Gln11Leu polymorphism situated on exon 3. SNP genotyping of the TLR7 exon polymorphism was performed by TaqMan allelic discrimination using the StepOnePlus™ Real-Time PCR System (Applied Biosystems). In females, the incidence of the AT genotypes of the polymorphism was significantly lower in sarcoidosis patients compared to control subjects (P=0.0001). We could observe in control subjects a significant preponderance of the T allele of the TLR7 rs179008/Gln11Leu polymorphism compared to sarcoidosis female patients (P=0.008). In males, no significant differences between patients and controls emerged in allele frequencies of the TLR7 rs179008/Gln11Leu polymorphism. The presence of the TLR7 rs179008/Gln11Leu polymorphism in sarcoidosis may determine an alteration of TLR7 function hampering the signaling pathway involved in the onset of both cellular and humoral autoimmunity. This is consistent with the view that in some circumstances genetic mutations affecting components of the immune system can prevent systemic autoimmunity.